Filsafat dan Gerakan Anti-Teror - Qusthan Firdaus (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
This article argues that research on terrorism conducted in educational institutions for the study of philosophy was just as impressed as the strategy and tactics of counter-terrorism to the anti-terror apparatus, in which, unfortunately, it has no coherent philosophical argumentation. It also reflects the the poor philosophical literature on terrorism. In other words, the promoter nor promovendus in PhD program equally ignorant about how to frame the issue of terrorism in the realm of philosophy. This condition is an advantage for the ideologues in the terror movement operating in Indonesia. Therefore, it is time for the Government of Indonesia led scholars and professors of philosophy to develop counter-terrorism argument through research grants adequate.